Agricultural development in India; issues, policies and prospects seminar proceedings and papers New Delhi Feb,13, 1997 - RGICS (New Delhi, 1997)
In the last half-decade, nature has been bountiful and as a result India has enjoyed good agricultural seasons. But all is not well with Indian agriculture. As the Ninth Plan approach paper points out, the country's "agricultural potential has not been nurtured. Investments in the agricultural sector, particularly...creation of irrigation potential has fallen short of targets. The strain on the agricultural economy is now beginning to show. The production of foodgrains for 1995/96 has declined.... The percentage of shortfall in irrigation capacity expansion during the Eighth Plan has been the highest". Apart from this, low productivity of Indian agriculture and a host of other inadequacies could be added to the list. In recent years, more subsidies are being given to the agricultural sector instead of increased investments in developing canals, wells, roads and other infrastructural facilities, teaching of farming techniques, and improving marketing and credit facilities. It would seem that a whole new strategy is required to stem this downslide in Indian agriculture. And it is this growing concern over the quality of growth, the marginalisation of the masses in its development, and the increasing efforts to make it capital intensive that led us to organise a one-day seminar, "Agricultural Development in India: Issues, Policies and Prospects" in February this year.
Keywords: Agriculture India economic aspects proceedings